Failure analysis and design optimization of alternator shaft used in rail coaches. (2021) - Anoop, M.S.; Dhanesh, S.
Abstract: The intension of this work is to conduct a failure analysis and optimize the design of the shaft in a 4.5KW alternator used in rail coaches. The shafts in alternator of rail coaches are continuously subjected to sudden and repeated loads. The alternator shaft is made from carbon steel rods supplied by SAIL (Steel Authority of India Limited) and is machined as per the design. This shaft is subjected to stress reversals and found to have failed in several occasions during the operation. Visual inspection of fractured surface showed cracks initiated from the stepped surface. The breakage occurs at the specific region where the stress concentration is high. The stress concentration is also due to the tool marking seen in the machined surface of the fillet region of the shaft. Under the different test conditions, the various problems related to the finish and design of the shaft was observed. According to the observation, failure and design problems of the shaft will be analyzed using finite element method based on which an alternate design is suggested. In this analysis, we consider only bending load on two dimensional axi-symmetrical model of the shaft.